Concentration of ms medium and cutting of seeds on in vitro establishment of baruzeiro (Dipteryx alata Vog.) - Pinhal, Hernane Fernandes (2017)
Savannah is the second biome in biodiversity in Brazil, presenting great vegetation endemism. Baruzeiro (Dipteryx alata Vog.), native from this biome, is an economically important species, with an incipient market due to the lack of commercial plantations. This highlights the need to develop and provide the basis for the domestication of this species. Thus, this study evaluated different concentrations of MS medium, using baruzeiro intact or cut seeds for in vitro establishment. Seeds from baruzeiro ripe fruits were decontaminated and were left intact or partially cut; subsequently, the seeds were inoculated into flasks with different concentrations of MS culture medium. The experimental design was completely randomized as a 5 x 2 factorial, consisting of 5 MS medium concentrations (0, 25, 50, 75 or 100%) and 2 types of seeds (intact or partially cut seeds), with three replications. Each experimental unit consisted of five flasks and 10 plants. After five months of incubation, the contamination of explants, seed germination, the number of fully developed plants and the dry masses of shoot and root of baruzeiros were evaluated. Intact seeds provided better results for all characteristics evaluated. The increased concentration of MS medium resulted in mass gain of plants; however, the use of MS medium 0% provided greater percentage of fully developed plants, the most interesting feature for baruzeiro in vitro establishment.